A new species of Ituglanis from the Rio Xingu basin, Brazil, and the evolution of pelvic fin loss in trichomycterid catfishes (Teleostei: Siluriformes: Trichomycteridae) - Datovo, Aléssio (Zootaxa, 2014)
A new species of the trichomycterid catfish genus Ituglanis is described from the Rio Curuá, Rio Xingu basin, Rio Amazonas drainage, Brazil. Ituglanis apteryx, new species, is promptly distinguished from congeners, except some specimens of I. parahybae (Eigenmann), by the absence of pelvic fins, girdle, and muscles. The new species differs from I. parahybae in the pattern of the cephalic laterosensory system; the absence of a posterior cranial fontanel; the presence of an epural; and the number of branchiostegal rays, ribs, and vertebrae. Ituglanis apteryx is one among the several trichomycterids lacking pelvic fins. Analysis reveals that pelvic fin loss independently evolved several times during the trichomycterid radiation.